2022
DOI: 10.21873/anticanres.16011
|View full text |Cite
|
Sign up to set email alerts
|

Critique of Public Health Guidance for Vitamin D and Sun Exposure in the Context of Cancer and COVID-19

Abstract: Official public health pronouncements about sun exposure and vitamin D can be summarized as follows: First, there is no such thing as a safe tan. Therefore, avoid exposing the skin to sunshine. Second, in the absence of sunshine, a daily intake of 800 IU/day (20 mcg/d) vitamin D or less is sufficient for the health needs of almost all members of the population. However, exposure of the skin to sunlight induces multiple mechanisms that lower blood pressure, while also initiating production of vitamin D, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The supplementation regimen we used was highly effective in correcting this among participants randomized to the intervention arm of the trial. Weekly administration of vitamin D 3 allowed us to directly observe and optimize adherence during term-time while avoiding large fluctuations in 25(OH)D that may result from larger and more widely spaced bolus doses used in some other studies and potential enzymatic dysregulation that could attenuate vitamin D’s pharmacological activity . Other important strengths of our study were the high retention rate (91.7% over 3 years) and standardization of serum 25(OH)D measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation regimen we used was highly effective in correcting this among participants randomized to the intervention arm of the trial. Weekly administration of vitamin D 3 allowed us to directly observe and optimize adherence during term-time while avoiding large fluctuations in 25(OH)D that may result from larger and more widely spaced bolus doses used in some other studies and potential enzymatic dysregulation that could attenuate vitamin D’s pharmacological activity . Other important strengths of our study were the high retention rate (91.7% over 3 years) and standardization of serum 25(OH)D measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Although almost all PCS patients experience vitamin D deficiency, no correlation was found between vitamin D levels and severity of PCS symptoms ( Mohamed Hussein et al, 2022 ). Nevertheless, supplementation of 2,000 IU daily is recommended for patients with vitamin D blood levels below 30 ng/mL ( Vieth, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Laaksi et al [ 44 ] and Urashima et al [ 45 ] showed that participants who ingested daily low-dose vitamin D 3 (400 IU and 1,200 IU, respectively) had a positive effect on URTI. Mechanistic insight into the difference between high bolus versus daily intake was provided by Vieth et al [ 46 ] suggesting that high-dose vitamin D 3 intake could induce substantial fluctuations in the concentration of serum 25(OH)D 3 , differently than daily low-dose vitamin D 3 intake, through an imbalance in the vitamin D regulating enzymes (CYP27B1 and CYP24A1). This results in a decreased level of active vitamin D (1,25(OH) 2 D 3 ) needed to assist the immune system against pathogens in respiratory infections and in this way, high-dose bolus vitamin D may impair immune function.…”
Section: Discussionmentioning
confidence: 99%